Factor Associated With The Occurrence Of Ari In Toddlers In The Working Area Of Telaga Dewa Health Center, Bengkulu City - Mrlina, Anggun Cahya; Fauzi, Yusran; Sari, Fikitri Marya; wulandari, Wulandari; Suyanto, Jipri (Journal Hygeia Public Health, 2024)
Intoduction: Acute respiratory infections (ARI) are the most common diseases causing death in toddlers, making ARI a significant cause of mortality. It is estimated that 13 million people die from ARI each year. The highest prevalence of ARI in Indonesia is found in five provinces: East Nusa Tenggara at 15.4% of the population, Banten at 11.9%, West Papua at 12.3%, Papua at 13.1%, and Bengkulu at 11.8%. This study aims to identify the risk factors associated with the occurrence of ARI in the working area of Telaga Dewa Health Center, Bengkulu City. Method: This study employs a quantitative approach with a cross-sectional design.The sample consists of 65 individuals, selected through purposive sampling. Data analysis was performed using chi-square tests with a significance level of 95%.Result and Discussion: Univariate analysis results show that 27 (41.5%) individuals did not receive exclusive breastfeeding, 15 (23.1%) experienced low birth weight (LBW), and 8 (12.3%) had a basic education level. Bivariate analysis results indicate a significant relationship between exclusive breastfeeding with a p-value of 0.001, LBW with a p-value of 0.007, and no relationship between education level with a p-value of 0.172 concerning the incidence of ARI < α 0.05 in the working area of Telaga Dewa Health Center, Bengkulu City. Conclusion: In this study it can be concluded that more people who do not give exclusive breastfeeding experience LBW compared to those who do not give exclusive breast milk, and there is a significant difference between giving exclusive breast milk and there is no relationship between the level of education and the incidence of ARI in the working area of ​​the Telaga Dewa Community Health Center.